ANALISIS PEMAHAMAN MATEMATIKA DASAR MAHASISWA PGSD - Dwi Widyastuti Nurharyanto; Iwan Abdy (Universitas Muhammadiyah Surabaya, 2025)
This research is research conducted to measure the extent to which students of the Primary School Teacher Education Study Program as prospective teachers are able to understand the basics of mathematics. These basic mathematics skills support career development as a teacher in the future. This research is a type of descriptive research with qualitative analysis. By giving a basic mathematics skills test at the start of learning, lecturers can find out which material requires in-depth study. The instrument used is a test instrument consisting of forty questions. The questions cover four main subjects, namely addition and subtraction, multiplication and division, LCM and FPB, and fractional numbers. The results of the tests given showed that the basic mathematics abilities of 36 students were seven students in the good category, 17 students in the sufficient category, and 12 students in the poor category. The material that is least mastered is the KPK and FPB material and fractional numbers. Based on these results, material strengthening can be focused on these two material categories. This research also includes a diagnostic test to create more ideal learning conditions because it can be adjusted to suit needs.